Analysis of nocturnal hypokinesia and sleep quality in Parkinson's disease. (August 2018) - Xue, Fei; Wang, Fu-Yu; Mao, Cheng-Jie; Guo, Si-Ping; Chen, Jing; Li, Jie; Wang, Qiao-Jun; Bei, Hong-Zhe; Yu, Qian; Liu, Chun-Feng
Highlights: Multisite inertial sensors can be used to quantitatively evaluate nocturnal motor functions in PD patients. Number and degree of turns showed greater significance than other parameters. UPDRS axial scores and the number of turns were two significant factors affecting sleep quality. Abstract: Nocturnal hypokinesia/akinesia and sleep disorder are believed to be common in Parkinson's disease (PD), but are often underestimated. To date, only a few studies have focused on nocturnal symptoms related to motor function and sleep quality in PD patients, and the assessments were based mainly on the subjective descriptions of the patients. In this study, we assessed the relationships between motor symptoms and sleep quality in 29 PD patients (17 PD patients reporting impaired bed mobility (IBM) and 12 patients without IBM). All the participants were monitored using multisite inertial sensors and polysomnography in sleep-monitoring rooms for whole night. Compared with PD−IBM patients, PD+IBM patients tended to have fewer turning-over episodes and smaller degree turns. Meanwhile, PD+IBM patients had worse Pittsburgh Sleep Quality Index (PSQI) and Parkinson's Disease Sleep Scale (PDSS) scores, and less total sleep time (TST) than PD−IBM patients. Spearman correlation analyses found that the number of turning-over events showed negative correlations with disease duration (r = −0.378, P  < 0.05) and Unified Parkinson's Disease Rating Scale (UPDRS) axial scores (r = −0.370, P  < 0.05). Moreover, TST (r = 0.505, p  < 0.05) and sleep efficiency (SE) (r = 0.473, p  < 0.05) positively correlated with the number of turns in bed. Multivariate linear regression analyses showed that UPDRS axial scores and the number of turns were significantly associated with TST (both p  < 0.05). In conclusion, the number of turns in bed and UPDRS axial scores were two significant factors affecting sleep quality. Multisite inertial sensors can be used to quantitatively evaluate nocturnal motor functions in PD patients.